To find the solution fo the given system of linear equation,
Let's substitute the equation y = 2x to y - x =1. We get,
![\text{ y - x = 1 }\rightarrow\text{ (2x) - x = 1}](https://img.qammunity.org/2023/formulas/mathematics/college/xmps3dduu43gjzlpw0rvn5jr8md0ykkjzt.png)
![\text{ x = 1}](https://img.qammunity.org/2023/formulas/mathematics/college/jr7rx8wc7dnbwcul273l3xi27o1xlx90gq.png)
Let's now find the value of y by substituting x = 1 to y =2x.
![\text{ y =2x }\rightarrow\text{ y = 2(1)}](https://img.qammunity.org/2023/formulas/mathematics/college/zmjtjh9ozx0pc93milxnlmbcglx9fm7999.png)
![\text{ y = 2}](https://img.qammunity.org/2023/formulas/mathematics/college/nn3vdopdzx4l7uhe2ef6bixy4srh9hnf8a.png)
Therefore, the system of the linear equation has one solution and it is (1,2).